A puncture-resistant self-healing composite material and a preparation method thereof
Patent Information
- Application Number
- CN202510424470.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-04-07
AI Technical Summary
[0003]1.界面结合强度不足:金属与高分子材料因热膨胀系数差异易分层;
[0030] This invention achieves the following technical effects through gradient modulus design, multi-scale interface strengthening technology, and a dynamic repair-energy dissipation synergistic mechanism:
Smart Images

Figure HDA0005346295170000011
Abstract
Description
Technical Field
[0001] This invention relates to the field of advanced functional composite materials technology, specifically to a puncture-resistant, self-healing composite material and its preparation method. Background Technology
[0002] Traditional puncture-resistant materials (such as metal plates and UHMWPE) suffer from problems such as heavy weight, poor flexibility, and irreversible damage. While existing self-healing materials (such as dynamically cross-linked TPU) can repair microcracks, their puncture resistance is insufficient. The current technical challenges lie in:
[0003] 1. Insufficient interfacial bonding strength: Metals and polymers are prone to delamination due to the difference in their coefficients of thermal expansion;
[0004] 2. Conflict between self-healing and puncture resistance: self-healing requires flexible materials, while puncture resistance requires high rigidity;
[0005] 3. Process complexity: Microstructure design is difficult to be compatible with large-scale production.
[0006] This invention addresses the aforementioned problems through gradient modulus design, multi-scale interface enhancement technology, and a dynamic repair-energy dissipation synergistic mechanism.
[0007] To this end, a puncture-resistant, self-healing composite material and its preparation method are proposed. Summary of the Invention
[0008] The present invention aims to solve the problems mentioned in the background art by providing a puncture-resistant, self-healing composite material and its preparation method.
[0009] The specific technical solution is as follows:
[0010] A puncture-resistant, self-healing composite material, comprising:
[0011] A gradient modulus three-layer structure, comprising an outer layer, a middle layer, and an inner layer, wherein:
[0012] The outer layer is a self-healing thermoplastic polyurethane (TPU) containing dynamic bonds, with a modulus of 1-2 GPa;
[0013] The intermediate layer is a titanium alloy woven mesh with microgrooves etched on the surface, and its modulus is 110 GPa.
[0014] The inner layer is an epoxy resin modified TPU adhesive layer containing a silane coupling agent;
[0015] The titanium alloy woven mesh has a wire diameter of 0.08 mm and a weaving density of 60×60 wires / cm. 2 The surface is treated with plasma to generate hydroxyl (-OH) groups, and mechanical interlocking grooves with a width of 20μm and a depth of 5μm are formed by laser etching.
[0016] The outer layer, the middle layer, and the inner layer are mechanically interlocked and covalently bonded to titanium silicon oxide (Si-O-Ti), with a total thickness of 0.25-0.3 mm.
[0017] The aforementioned puncture-resistant self-healing composite material contains a layer of outer self-healing TPU in which the dynamic bonds are selected from Diels-Alder (DA) bonds or ureidopyrimidinone (UPy) hydrogen bonds, and 0.1-0.5 wt% of zinc oxide (ZnO) nanoparticles are added as a photothermal catalyst.
[0018] The aforementioned puncture-resistant self-healing composite material contains an epoxy resin-modified TPU inner adhesive layer containing 1-2 wt% silane coupling agent KH-550, which forms Si-O-Ti covalent bonds with the intermediate titanium mesh through a vacuum hot pressing process.
[0019] The aforementioned puncture-resistant, self-healing composite material, wherein the titanium alloy woven mesh is replaced with a Z-shaped woven structure or an I-shaped 3D knitted structure filled with carbon fiber sheets, wherein the warp and weft density of the Z-shaped weave is 60×60 threads / cm. 2 The cavity spacing of the I-shaped 3D knit is 1.5-4cm.
[0020] This invention also provides a method for preparing a puncture-resistant, self-healing composite material, comprising the following steps:
[0021] a) The titanium alloy wire was subjected to plasma treatment with the following parameters: argon (Ar) atmosphere, 100W power, and 5 minutes. This was followed by nanosecond pulsed laser treatment (wavelength 1064nm, energy density 2J / cm²). 2 Etching surface grooves;
[0022] b) Molten self-healing TPU is coated on both sides of the pretreated titanium mesh at 180°C and then cold-pressed at 10MPa pressure to below 40°C.
[0023] c) The inner adhesive layer and the intermediate layer are laminated by vacuum hot pressing, with parameters of 80℃, 5MPa, and holding pressure for 10 minutes.
[0024] The above-mentioned method for preparing puncture-resistant self-healing composite material includes a laser etching system using a multi-beam parallel system with an etching speed ≥0.5m / min and a distance of 10cm between the titanium mesh conveyor belt and the laser head.
[0025] In the above-mentioned method for preparing puncture-resistant self-healing composite material, the surface roughness Ra of the titanium alloy woven mesh is <1μm, and the plasma treatment depth is ≤50nm to avoid embrittlement of the titanium mesh.
[0026] The above-mentioned method for preparing puncture-resistant self-healing composite material includes adding 0.3 wt% of hydrophobic agent KH-570 to the inner adhesive layer, so that the peel strength retention rate is ≥90% after aging at 85℃ / 85% relative humidity (RH) for 500 hours.
[0027] The above-mentioned method for preparing puncture-resistant self-healing composite material, wherein the melt index (MFI) of the outer self-healing TPU is 15 g / 10 min, and water cooling process is used to control internal stress during cold pressing and shaping.
[0028] The above-mentioned method for preparing puncture-resistant self-healing composite material, wherein the puncture-resistant self-healing composite material is not penetrated under 50J impact energy (NIJ0115.00 standard), and the air tightness recovery rate is ≥95% after 24 hours at room temperature or 2 hours of near-infrared light irradiation.
[0029] The present invention has the following beneficial effects:
[0030] This invention achieves the following technical effects through gradient modulus design, multi-scale interface strengthening technology, and a dynamic repair-energy dissipation synergistic mechanism:
[0031] 1. Performance Co-optimization:
[0032] Puncture resistance: The outer TPU viscoelastic dissipation (loss factor tanδ=0.3) and the plastic deformation of the titanium mesh (70% energy absorption) work synergistically to resist 50J impact without penetration (NIJ0115.00 standard);
[0033] Self-healing capability: UPy hydrogen bonds can be repaired at room temperature for 24 hours or DA bonds can be repaired by near-infrared light for 2 hours, with an airtightness recovery rate of ≥95% (nitrogen leakage rate <5×10). -6 mbar·L / s).
[0034] 2. Interface enhancement and stability:
[0035] Mechanical-chemical double bonding: Laser-etched grooves (20μm wide / 5μm deep) form a mechanical interlock, combining Si-O-Ti covalent bonds (KH-550 coupling), with a peel strength ≥12N / cm;
[0036] Environmental tolerance: After adding KH-570 hydrophobic agent, the peel strength retention rate after wet heat aging (85℃ / 85%RH, 500h) is ≥90%.
[0037] 3. Process innovation and cost control:
[0038] High-efficiency etching: The multi-beam laser system (≥6 parallel heads) increases the etching speed to ≥0.5m / min with an accuracy error of <±2μm;
[0039] Lightweight design: The amount of titanium mesh used is reduced by 30% (compared to traditional metal layers), and TPU is recyclable, effectively reducing raw material costs.
[0040] 4. Diverse and adaptable structures:
[0041] Weave variant: Z-shaped weave increases shear strength by 25%, and I-shaped 3D knitting filled with carbon fiber sheets enhances multi-directional impact resistance;
[0042] Functional expansion: Photothermal catalysis of ZnO nanoparticles (0.1-0.5wt%) enables on-demand triggered repair, adapting to scenarios such as flexible electronic packaging.
[0043] This material can be widely used in bulletproof vests, protective clothing, aerospace flexible armor, flexible electronic packaging and other fields, and is especially suitable for scenarios that require lightweight, high protection and self-maintenance. Attached Figure Description
[0044] Figure 1 This is a schematic diagram of the puncture-resistant, self-healing composite material provided in an embodiment of the present invention.
[0045] In the attached image:
[0046] 1. Outer layer; 2. Middle layer; 3. Inner layer. Detailed Implementation
[0047] The technical solution of the present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0048] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual images. They should not be construed as limiting the scope of this patent. To better illustrate the embodiments of the present invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual dimensions of the product. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.
[0049] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "inner," and "outer" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present patent. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.
[0050] In the description of this invention, unless otherwise explicitly specified and limited, the term "connection" or similar designation indicating a connection between components should be interpreted broadly. For example, it can refer to a fixed connection, a detachable connection, or an integral part; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can refer to the internal communication between two components or the interaction between two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0051] The puncture-resistant, self-healing composite material provided by this invention, such as... Figure 1 As shown, it includes: a gradient modulus three-layer structure, which consists of an outer layer 1, a middle layer 2, and an inner layer 3, wherein:
[0052] The outer layer 1 is a self-healing thermoplastic polyurethane (TPU) containing dynamic bonds, with a modulus of 1-2 GPa;
[0053] The intermediate layer 2 is a titanium alloy woven mesh with microgrooves etched on the surface, and its modulus is 110 GPa.
[0054] Inner layer 3 is an epoxy resin modified TPU adhesive layer containing silane coupling agent;
[0055] The titanium alloy woven mesh has a wire diameter of 0.08mm and a weaving density of 60×60 wires / cm. 2 The surface is treated with plasma to generate hydroxyl (-OH) groups, and mechanical interlocking grooves with a width of 20μm and a depth of 5μm are formed by laser etching.
[0056] The outer layer 1, the middle layer 2, and the inner layer 3 are mechanically interlocked and covalently bonded to silicon-oxygen-titanium (Si-O-Ti), with a total thickness of 0.25-0.3 mm.
[0057] The puncture-resistant, self-healing composite material provided by the above solution, through a gradient modulus design (outer layer 1-2 GPa, middle layer 110 GPa, inner layer 5-8 GPa), achieves a stepwise transfer of impact energy from viscoelastic dissipation in the flexible outer layer → plastic deformation of the rigid titanium mesh → stable interface in the inner layer, synergistically improving puncture resistance (no penetration at 50J) and self-healing efficiency (air tightness recovery ≥95%). Plasma treatment of the titanium mesh surface and laser-etched grooves (20 μm wide, 5 μm deep) form a multi-scale mechanical interlock, combined with Si-O-Ti covalent bonds, resulting in an interfacial peel strength ≥12 N / cm, solving the delamination problem of traditional materials.
[0058] Among them, the dynamic bonds in the outer layer 1 self-healing TPU are selected from Diels-Alder (DA) bonds or ureidopyrimidinone (UPy) hydrogen bonds, and 0.1-0.5wt% of zinc oxide (ZnO) nanoparticles are added as photothermal catalysts. When ZnO nanoparticles (0.1-0.5wt%) are used as photothermal catalysts, the photothermal conversion efficiency is ≥40% under 808nm near-infrared light irradiation, which significantly accelerates the dynamic exchange of DA bonds and shortens the repair time from 24h (room temperature) to 2h, without affecting the flexibility of the TPU layer.
[0059] The inner 3 adhesive layer contains 1-2 wt% of epoxy resin modified TPU with silane coupling agent KH-550, which forms Si-O-Ti covalent bonds with the intermediate titanium mesh through a vacuum hot pressing process. The 1-2 wt% KH-550 coupling agent in the epoxy resin modified TPU forms Si-O-Ti covalent bonds with the titanium mesh -OH groups through vacuum hot pressing (80℃ / 5MPa), combined with mechanical interlocking, which improves the interfacial bonding strength by 30%. After wet heat aging, the peel strength retention rate is ≥90%, avoiding adhesion failure caused by hydrolysis.
[0060] Specifically, the titanium alloy woven mesh is replaced with a Z-shaped woven structure or an I-shaped 3D knitted structure filled with carbon fiber sheets, wherein the warp and weft density of the Z-shaped weave is 60×60 threads / cm. 2 The cavity spacing of the I-shaped 3D knit is 1.5-4cm, and the Z-shaped weave (warp and weft angle 110°-120°) enhances the shear strength by 25% through fiber interlacing; the cavity of the I-shaped 3D knit (1.5-4cm spacing) is filled with carbon fiber sheets to improve multi-directional impact resistance, while reducing the material surface density by 10%-15%.
[0061] This invention also provides a method for preparing a puncture-resistant, self-healing composite material, comprising the following steps:
[0062] a) The titanium alloy wire was subjected to plasma treatment with the following parameters: argon (Ar) atmosphere, 100W power, and 5 minutes. This was followed by nanosecond pulsed laser treatment (wavelength 1064nm, energy density 2J / cm²). 2 Etching surface grooves;
[0063] b) Molten self-healing TPU is coated on both sides of the pretreated titanium mesh at 180°C and then cold-pressed at 10MPa pressure to below 40°C.
[0064] c) The inner adhesive layer and the intermediate layer are laminated by vacuum hot pressing, with parameters of 80℃, 5MPa, and holding pressure for 10 minutes.
[0065] The preparation method of this puncture-resistant, self-healing composite material involves plasma treatment (Ar / 100W / 5min) to generate -OH groups, combined with nanosecond laser etching (1064nm / 2J / cm). 2 To control the surface roughness Ra < 1 μm, avoid titanium mesh embrittlement (processing depth ≤ 50 nm), ensure the uniformity of groove morphology, and significantly improve TPU filling rate.
[0066] The laser etching process employs a multi-beam parallel system with an etching speed ≥0.5m / min. The distance between the titanium mesh conveyor belt and the laser head is 10cm. The multi-beam parallel (≥6 heads) laser etching system increases the single etching speed from 0.2m / s to ≥0.5m / min, improving production efficiency by 3 times. Furthermore, the groove size error is <±2μm, meeting the requirements for large-scale production.
[0067] Among them, the surface roughness Ra of the titanium alloy woven mesh is <1μm, and the plasma treatment depth is ≤50nm to avoid the titanium mesh from becoming brittle. The surface roughness Ra of the titanium mesh is <1μm (Ra=1.2μm after plasma treatment), which optimizes the flowability of TPU melt, makes the groove filling depth ≥5μm, and significantly improves the mechanical interlocking strength.
[0068] The inner layer 3 adhesive layer contains 0.3 wt% of hydrophobic agent KH-570, which makes the peel strength retention rate ≥90% after aging at 85℃ / 85% relative humidity (RH) for 500 hours. The addition of 0.3 wt% KH-570 hydrophobic agent in the inner layer makes the material contact angle ≥110°, blocking water molecules from penetrating the interface. After humid heat aging (85℃ / 85%RH, 500h), the peel strength retention rate is increased from 50% to ≥90%.
[0069] The outer layer 1 self-healing TPU has a melt index (MFI) of 15g / 10min. During the cold pressing process, water cooling is used to control internal stress. The melt index MFI is 15g / 10min (melting at 180℃). Combined with 10MPa cold pressing and water cooling (cooling to 30℃), internal stress is eliminated, and the interlayer thickness error is ≤±0.01mm, avoiding performance fluctuations caused by thermal degradation.
[0070] Among them, the puncture-resistant self-healing composite material was not penetrated under 50J impact energy (NIJ0115.00 standard), and the airtightness recovery rate was ≥95% after 24 hours at room temperature or 2 hours of near-infrared light irradiation. This was achieved through the viscoelastic dissipation of the outer TPU layer (loss factor tanδ=0.3) and the plastic deformation of the titanium mesh (70% energy absorption), resulting in no penetration under 50J impact (NIJ0115.00 standard). After room temperature repair of UPy hydrogen bonds or photothermal repair of DA bonds, the nitrogen leakage rate was <5×10⁻⁶. -6 mbar·L / s, meeting the hermeticity requirements of flexible electronic packaging.
[0071] The present invention also provides the following embodiments 1-6:
[0072] Example 1 (Laboratory Grade)
[0073] Steps and parameters:
[0074] 1. Titanium mesh pretreatment:
[0075] Titanium wire specifications: TA2 pure titanium, wire diameter 0.08mm;
[0076] Plasma treatment: Argon atmosphere, power 100W, time 5 minutes, hydroxyl (-OH) groups are generated on the surface;
[0077] Laser etching: Nanosecond pulsed laser (wavelength 1064nm, energy density 2J / cm²) 2 The scanning speed is 0.2 m / s, the groove size is 20 μm wide and 5 μm deep, and the roughness Ra = 1.2 μm.
[0078] 2. TPU coating:
[0079] Outer TPU: BASF Add 1.5 wt% silane coupling agent KH-550 and 0.3 wt% ZnO nanoparticles;
[0080] Melting temperature: 180℃ (MFI = 15g / 10min), double-sided titanium mesh coating.
[0081] 3. Composite process:
[0082] Cold pressing: Pressure 10MPa, water cooling to 30℃ to eliminate internal stress;
[0083] Vacuum hot-pressed adhesive layer: Huntsman Modified TPU (containing 1.2wt% KH-550), parameters: 80℃, 5MPa, holding pressure for 10 minutes.
[0084] 4. Performance Testing:
[0085] Peel strength: 13.5 N / cm (ASTM D903 standard);
[0086] Puncture resistance: No penetration under 55J impact energy (NIJ0115.00 standard);
[0087] Self-repair efficiency: After 2 hours of 808nm near-infrared light irradiation, the airtightness recovery rate is 97% (nitrogen leakage rate < 4 × 10⁻⁶). - 6 mbar·L / s).
[0088] Example 2 (Production Line Level)
[0089] Steps and parameters:
[0090] 1. Titanium mesh pretreatment:
[0091] Employing a multi-beam laser system (6 heads in parallel), the etching speed is increased to 0.6 m / min;
[0092] The plasma processing parameters are the same as in Example 1.
[0093] 2. Functional modification:
[0094] The inner adhesive layer is enhanced with 0.3wt% KH-570 hydrophobic agent to improve stability in humid and hot environments.
[0095] 3. Composite process:
[0096] The parameters for cold pressing and vacuum hot pressing are the same as in Example 1, but an automated feeding system is used, increasing the production rate to 20m / h.
[0097] 4. Performance Testing:
[0098] Damp heat aging test: After aging at 85℃ / 85%RH for 500 hours, the peel strength retention rate was 91%;
[0099] Consistency in large-scale production: 10 batches of samples were tested, and the puncture resistance (50J without penetration) achieved a 100% compliance rate.
[0100] Example 3 (Verification of Z-shaped weave structure)
[0101] Steps and parameters:
[0102] 1. Replacement with titanium mesh structure:
[0103] Z-shaped woven titanium mesh (warp and weft density 60×60 threads / cm) 2 (Weaving angle 115°);
[0104] The wire diameter is 0.08 mm, and the surface treatment process is the same as in Example 1.
[0105] 2. Composite process:
[0106] The formulations of the outer TPU layer and the inner adhesive layer are the same as in Example 1.
[0107] 3. Performance Testing:
[0108] Shear strength: 27% higher than plain weave (from 180MPa to 229MPa);
[0109] Multi-directional impact test: Under a 30J oblique impact, the penetration depth is reduced by 40% (from 8mm to 4.8mm).
[0110] Example 4 (Optimization of Photothermal Restoration Efficiency)
[0111] Steps and parameters:
[0112] 1. TPU modification:
[0113] The ZnO nanoparticle content in the outer TPU layer increased to 0.5 wt%;
[0114] The depth of the laser-etched groove was adjusted to 8 μm (other parameters are the same as in Example 1).
[0115] 2. Repair conditions:
[0116] Near-infrared light intensity: 1.5 W / cm² 2 (wavelength 808nm), repair time gradient test (0.5h, 1h, 2h).
[0117] 3. Performance Testing:
[0118] Repair efficiency: 95% airtightness recovery rate after 1 hour of light exposure, and 99% after 2 hours;
[0119] Thermal stability: The repaired area showed no secondary cracking during cyclic testing from -20℃ to 80℃.
[0120] Example 5 (Extreme Environment Tolerance Verification)
[0121] Steps and parameters:
[0122] 1. Environmental testing:
[0123] High temperature and high humidity: 70℃ / 95%RH, for 1000 hours;
[0124] Low temperature shock: After freezing at -40℃ for 24 hours, immediately conduct a 50J puncture resistance test.
[0125] 2. Performance Testing:
[0126] Peel strength retention rate: 88% after high temperature and high humidity, and no decrease in peel strength after low temperature impact;
[0127] Puncture resistance: Still meets 50J non-penetration requirement (NIJ standard) even at low temperatures.
[0128] Example 6 (I-shaped 3D knitted structure)
[0129] Steps and parameters:
[0130] 1. Replacement with titanium mesh structure:
[0131] The material is an I-shaped 3D knitted titanium mesh with a cavity height of 2mm, filled with carbon fiber sheets (spaced 2cm apart); the surface treatment process is the same as in Example 1.
[0132] 2. Composite process:
[0133] The thickness of the inner adhesive layer was increased to 0.06 mm to accommodate the cavity structure.
[0134] 3. Performance Testing:
[0135] Areal density: reduced by 12% (from 2.8 kg / m³) 2 Reduced to 2.46 kg / m 2 );
[0136] Multidirectional impact resistance: Under a 45J impact, the energy absorption rate is increased by 18% (compared to a plain weave structure). This is verified through the above embodiments.
[0137] Structural adaptability: Z-shaped and I-shaped weaving can respectively improve shear strength and lightweight performance;
[0138] Repair controllability: ZnO content and light intensity synergistically regulate the repair speed;
[0139] Environmental robustness: Stable performance over a wide temperature range of -40℃ to 85℃ and in high humidity environments;
[0140] Scalability feasibility: The multi-beam laser system and automated production line ensure efficient and high-precision manufacturing. In summary, the puncture-resistant self-healing composite material and its preparation method provided in this embodiment have the following advantages:
[0141] This invention achieves the following technical effects through gradient modulus design, multi-scale interface strengthening technology, and a dynamic repair-energy dissipation synergistic mechanism:
[0142] 1. Performance Co-optimization:
[0143] Puncture resistance: The outer TPU viscoelastic dissipation (loss factor tanδ=0.3) and the plastic deformation of the titanium mesh (70% energy absorption) work synergistically to resist 50J impact without penetration (NIJ0115.00 standard);
[0144] Self-healing capability: UPy hydrogen bonds can be repaired at room temperature for 24 hours or DA bonds can be repaired by near-infrared light for 2 hours, with an airtightness recovery rate of ≥95% (nitrogen leakage rate <5×10-6mbar·L / s).
[0145] 2. Interface enhancement and stability:
[0146] Mechanical-chemical double bonding: Laser-etched grooves (20μm wide / 5μm deep) form a mechanical interlock, combining Si-O-Ti covalent bonds (KH-550 coupling), with a peel strength ≥12N / cm;
[0147] Environmental tolerance: After adding KH-570 hydrophobic agent, the peel strength retention rate after wet heat aging (85℃ / 85%RH, 500h) is ≥90%.
[0148] 3. Process innovation and cost control:
[0149] High-efficiency etching: The multi-beam laser system (≥6 parallel heads) increases the etching speed to ≥0.5m / min with an accuracy error of <±2μm;
[0150] Lightweight design: The amount of titanium mesh used is reduced by 30% (compared to traditional metal layers), and TPU is recyclable, effectively reducing raw material costs.
[0151] 4. Diverse and adaptable structures:
[0152] Weave variant: Z-shaped weave increases shear strength by 25%, and I-shaped 3D knitting filled with carbon fiber sheets enhances multi-directional impact resistance;
[0153] Functional expansion: Photothermal catalysis of ZnO nanoparticles (0.1-0.5wt%) enables on-demand triggered repair, adapting to scenarios such as flexible electronic packaging.
[0154] Technical advantages
[0155] puncture resistance Metal plate (50J, penetration depth > 15mm) 50J non-penetrating (NIJ standard) Self-repair efficiency Microcrack repair requires >48 hours Repair at room temperature for 24 hours / photothermal for 2 hours Interface bonding strength ≤8N / cm (easily segregates) ≥12 N / cm (mechanical-chemical bonding) Environmental stability Strength retention rate after damp heat aging <50% ≥90% (KH-570 modified) Process cost High proportion of metal layer, non-recyclable Titanium mesh reduced by 30%, TPU is recyclable
[0156] This material can be widely used in bulletproof vests, protective clothing, aerospace flexible armor, flexible electronic packaging and other fields, and is especially suitable for scenarios that require lightweight, high protection and self-maintenance.
[0157] The above are merely preferred embodiments of the present invention and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should recognize that any equivalent substitutions and obvious changes made based on the description and illustrations of the present invention should be included within the protection scope of the present invention.
Claims
1. A puncture-resistant, self-healing composite material, characterized in that, include: A gradient modulus three-layer structure, comprising an outer layer (1), a middle layer (2), and an inner layer (3), wherein: The outer layer (1) is a self-healing thermoplastic polyurethane (TPU) containing dynamic bonds, with a modulus of 1-2 GPa; The intermediate layer (2) is a titanium alloy woven mesh with microgrooves etched on the surface, and the modulus is 110 GPa; The inner layer (3) is an epoxy resin modified TPU adhesive layer containing silane coupling agent; The outer layer (1), the middle layer (2) and the inner layer (3) are mechanically interlocked and covalently bonded to silicon-oxygen-titanium (Si-O-Ti), with a total thickness of 0.25-0.3 mm; The dynamic bonds in the outer layer (1) self-healing thermoplastic polyurethane (TPU) are selected from Diels-Alder bonds or ureidopyrimidinone hydrogen bonds, and 0.1-0.5 wt% of zinc oxide nanoparticles are added as photothermal catalysts.
2. The puncture-resistant, self-healing composite material according to claim 1, characterized in that, The titanium alloy woven mesh has a wire diameter of 0.08 mm and a weaving density of 60×60 wires / cm². The surface is treated with plasma to generate hydroxyl groups, and mechanical interlocking grooves with a width of 20 μm and a depth of 5 μm are formed by laser etching.
3. The puncture-resistant, self-healing composite material according to claim 1, characterized in that, The epoxy resin modified TPU in the inner layer (3) adhesive layer contains 1-2 wt% silane coupling agent KH-550, and forms Si-O-Ti covalent bonds with the intermediate titanium mesh through a vacuum hot pressing process.
4. A method for preparing a puncture-resistant self-healing composite material according to any one of claims 1-3, comprising the following steps: a) The titanium alloy wire was subjected to plasma treatment with parameters of argon atmosphere, power of 100W and time of 5 minutes, followed by nanosecond pulsed laser etching of surface grooves. b) Molten self-healing TPU is coated on both sides of the pretreated titanium mesh at 180°C and then cold-pressed at 10MPa pressure to below 40°C. c) The inner adhesive layer and the intermediate layer are laminated by vacuum hot pressing, with parameters of 80℃, 5MPa, and holding pressure for 10 minutes.
5. The method for preparing the puncture-resistant self-healing composite material according to claim 4, characterized in that, The laser etching employs a multi-beam parallel system with an etching speed ≥0.5m / min, and the distance between the titanium mesh conveyor belt and the laser head is 10cm.
6. The method for preparing the puncture-resistant self-healing composite material according to claim 4, characterized in that, The surface roughness Ra of the titanium alloy woven mesh is less than 1 μm, and the plasma treatment depth is less than 50 nm to avoid embrittlement of the titanium mesh.
7. The method for preparing the puncture-resistant self-healing composite material according to claim 4, characterized in that, The inner layer (3) adhesive layer contains 0.3wt% hydrophobic agent KH-570, so that the peel strength retention rate is ≥90% after the material is aged at 85℃ / 85% relative humidity for 500 hours.
8. The method for preparing the puncture-resistant self-healing composite material according to claim 4, characterized in that, The outer layer (1) has a melt index of 15 g / 10 min for self-healing TPU, and water cooling process is used to control internal stress during cold pressing and shaping.
9. The method for preparing the puncture-resistant self-healing composite material according to claim 4, characterized in that, The puncture-resistant, self-healing composite material was not penetrated under an impact energy of 50J, and its airtightness recovery rate was ≥95% after 24 hours at room temperature or 2 hours of near-infrared light irradiation.
Citation Information
Patent Citations
Composite material for stab, ice pick and armor applications
CN101243297A
Preparation method of porous netty ceramic reinforced steel and iron base composite lining plate
CN109317644A